Pengaruh Kombinasi Naphthalene Acetic Acid (NAA) –Benzyl Amino Purine (BAP) dan Jenis Eksplan pada Mikropropagasi Anggrek Vanda tricolor Lindl. var. suavis - AYU INDAH WIDAYANTI; RINDANG DWIYANI; HESTIN YUSWANTI (Fakultas Pertanian Universitas Udayana, 2014)
The Effect of Combination of BAP-NAA and Explant Types on Micropropagation of Orchidof Vanda tricolor Lindl. var. suavisThe objectives of the research was to investigate the effect ofcombination of NAA–BAP, type of explant and their interactions on shoot initiation in micropropagationof Vanda tricolor L. var. suavis. The factorial experiment consisted of two factors that was arrangedby completely randomized design (CRD) with three replications. The first factor was combination ofNAA-BAP i.e. M0= MS medium without any plant growth regulator; M1= MS + 0,1 mgL-1 NAA +0 mgL-1 BAP; M2= MS + 0,1 mgL-1 NAA + 0,1 mgL-1 BAP; M3= MS + 0,1 mgL-1 NAA + 1 mgL-1 BAP ; and M4= MS + 0,1 mgL-1 NAA + 10 mgL-1 BAP. The second factor was explant type i.e.shoot tip (B1) and shoot base (B2). The results showed that there was no interaction between factorsfor all variable observed. Medium M0 (MS medium without any plat growth regulator) and explant ofB1 (shoot tip) gave the highest number of the percentage of explants producing shoots and the highestnumber of shoots per explant.